1988
DOI: 10.3181/00379727-187-42659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bile Anionic Polypeptidic Fraction on the Fate of Cholesterol Carried by Liposomes in the Rat

Abstract: 14C]Cholesterol associated with liposomes with or without anionic polypeptidic fraction was administered intravenously to the rat. The cholesterol originated from liposomes including anionic polypeptidic fraction is secreted in bile much later, is stored in liver in higher quantity, and is metabolized into bile salts in lesser quantity during the 4 hr of experimentation than the cholesterol issued from liposomes exempt of anionic polypeptidic fraction. From these results it can be postulated that the cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Thus, we hypothesize that such discrepancy may imply the small hydrophobic APF [18] . Our deduction is consistent with previous reports describing several characteristics of APF in plasma [13,14,31] . This peptide, identifi ed as a minor HDL apolipoprotein, shares some common epitopes with apoA-I.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, we hypothesize that such discrepancy may imply the small hydrophobic APF [18] . Our deduction is consistent with previous reports describing several characteristics of APF in plasma [13,14,31] . This peptide, identifi ed as a minor HDL apolipoprotein, shares some common epitopes with apoA-I.…”
Section: Discussionsupporting
confidence: 83%
“…By contrast, we now observed a large inhibitory potential of the lipid-free APF at its physiological HDL 3 level, after stimulation with the calcium bound to heparin. This main fi nding suggests that one of the antiatherogenic mechanisms of APF could be related to its calcium antagonist ability [14] . The assumption is also consistent with previous reports showing that APF is able to reduce some metabolic effects of calcium observed in the bile in a dose-dependent manner [14] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that APF is involved in the uptake of unesterified cholesterol (15) and stimulates cholesterol and PL transport to the bile (16,17). It was also recently demonstrated that APF plays an important role in controlling the onset and rates of precipitation of calcium salts, bile pigments, and cholesterol in gallstone formation (18,19).…”
mentioning
confidence: 99%